Bioresorbable Polymers : Biomedical Applications - Devine, Declan (De Gruyter, 2019)
Bioresorbable implants can be processed via conventional polymer processing methods such as extrusion, injection and compressing moulding, solvent spinning or casting. This book addresses issues and highlights recent advances in the use of biodegradable polymers. It is intended for researchers utilizing biodegradable polymers in areas from tissue engineering to controlled release of active pharmaceuticals, as well as industrial processors.- Resumé vydavatel
Keywords: polymery; biomedicína; biologické materiály; polymers; biomedicine; biological materials; elektronické knihy; sborníky; electronic books; papers of several authors